Resistance mechanisms in BRAFV600E paediatric high-grade glioma and current therapeutic approaches - Lehmann, R.; Rayner, B. S.; Ziegler, D. S. (Frontiers in Oncology, 2022)
Paediatric high-grade gliomas (pHGG) are aggressive central nervous system tumours with a poor prognosis. BRAFV600E mutant pHGGs can be treated with targeted BRAF inhibitors, which have shown both preclinical activity and potent clinical efficacy. Unfortunately, the development of drug resistance results in disease relapse or progression and is the primary cause of treatment failure. While there is a lot of data to explain mechanisms of resistance in other BRAFV600E tumours, comparatively little is known about the mechanisms of BRAF inhibitor resistance in BRAFV600E pHGG. Recent literature has identified aberrations in members of the RAS/RAF/ERK pathway, the PI3K/AKT/MTOR pathway and the cell cycle as major contributors to the resistance profile. A range of novel therapies have been suggested to overcome BRAF inhibitor drug resistance in BRAFV600E pHGG. This review will discuss the current literature available for BRAF inhibitor resistant BRAFV600E pHGGs and provide an overview of the currently available and proposed therapies.